(untitled) (Papeles, 2025)
Introduction: Discrimination, prejudice, and stereotypes toward vulnerable groups directly affect social equity and human rights by perpetuating inequalities and limiting opportunities. The validation of measurement instruments ensures that theoretical constructs related to discrimination are assessed in a precise, reliable, and culturally relevant manner. Therefore, the objective of this study was to validate the factorial structure of scales derived from the National Survey on Discrimination (Enadis 2019), focused on measuring áreas of discrimination, agreement with prejudice, openness to diversity, and permissiveness toward discrimination. Methodology: The study followed a quantitative approach, with a non-experimental, ex post facto, and cross-sectional design. A total of 389 university students from various academic fields at a public university in northwestern Mexico participated. The instruments used were the Enadis (2019) scales on discrimination, tolerance, permissiveness, and empathy. Results and Discussion: Exploratory and confirmatory factor analyses were conducted, showing adequate indices of validity and reliability in most scales. The Tolerance scale showed the highest explained variance (72.7 %) and the most robust structure; the Permissiveness scale was refined to six items with good model fit; and the Empathy scale was divided into two differentiated factors, contributing to the design of evidence-based public policies. Conclusions: The findings support the of these scales as diagnostic tools in educational and social contexts. It is recommended to expand their application to diverse populations.